Unraveling distinct FO performance of NF-like membranes fabricated by deposition of bilayers containing polyamines with minor structural differences - Chen, Kai K. (2023)
Nanofiltration (NF)-like membranes have shown potential for implementing forward osmosis (FO) for resource recovery. Despite the popular use of poly(allylamine hydrochloride) (PAH) as a polycation in the layer-by-layer (LbL) coating of NF-like membranes, it remained ambiguous whether substantial changes could result from the minor structural difference in polyamine when employing polyvinylamine (PVAm) as the polycation. This study systematically assessed the filtration capability of the NF-like membranes with varying combinations of the PAH- and PVAm-containing bilayers in an FO process. The FO experiments revealed that the dominance of PVAm-containing bilayers in the upper part of the active layer could result in decreases in both the water permeability and the rejection of divalent salts. Subsequent fouling tests demonstrated that the membrane coated solely with PVAm-containing bilayers (i.e., the VVV membrane) exhibited the fastest flux decline in the fouling tests with sodium alginate (SA), whereas the fouling layer could be more easily removed by the crossflow. Optical coherence tomography (OCT) characterization indicated that the bridging effect of divalent cations could promote the aggregation of SA to form a particulate layer more susceptible to the shear effect. All the results shed light on the improvement of NF-like FO by regulating the formation of the active layer via the LbL assembly.